The Use of Small Group Discussion in Teaching Reading Comprehension at Junior High School - Ningsih, Suriana; Amin, Bahrun; Muhsin, Muh. Arief (Faculty of Education and Teacher Training of IAIN Palopo, 2021)
The background of this research is that the use of the small group discussion method is more effective than the preaching method in teaching reading comprehension. understanding because they can read more comprehensively with their friends in small groups and then discuss the information they have read. The purpose of this study was to determine the effect of student learning outcomes by using small group discussions in learning reading comprehension. This study uses a quantitative method by giving tests, namely pre-test and post-test to twenty eighth grade students at SMP Muhammadiyah Camba. This research applied a pre-experimental design. The test given to students is in the form of multiple-choice in the form of narrative text reading. The results of this study indicate that the experiment conducted by the researcher on students affects learning outcomes by Using Small Group Discussions in teaching reading comprehension. The average value in the pre-tests is 49.25 while the post-tests have an average value of 82.75. It was provided in the value of the t-test (8.152) which was greater than the value of the t-table (2.093). It indicated that there were significant differences, this is also indicated H1 was accepted and H0 was rejected.